2022
DOI: 10.3389/fpubh.2022.992046
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19 stigma during the onset of the global pandemic in India: A cross-sectional study

Abstract: ObjectiveTo assess factors associated with COVID-19 stigmatizing attitudes in the community and stigma experiences of COVID-19 recovered individuals during first wave of COVID-19 pandemic in India.MethodsA cross-sectional study was conducted in 18 districts located in 7 States in India during September 2020 to January 2021 among adults > 18 years of age selected through systematic random sampling. Data on socio demographic and COVID-19 knowledge were collected from 303 COVID-19 recovered and 1,976 non-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…16,17,1921,3335,37,39,41,42,44,47,48,53,56,57,60,73,76,88 In 16 studies blaming from others was the second most common social stigma reported due to being infected with COVID-19. 22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment. 29,33,37,44,46,47,50,56,60,73,76,80,83 Other stigmas experienced by COVID-19 patients included psychological pressure, 62,6672,75,79,81 verbal violence, 20,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17,1921,3335,37,39,41,42,44,47,48,53,56,57,60,73,76,88 In 16 studies blaming from others was the second most common social stigma reported due to being infected with COVID-19. 22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment. 29,33,37,44,46,47,50,56,60,73,76,80,83 Other stigmas experienced by COVID-19 patients included psychological pressure, 62,6672,75,79,81 verbal violence, 20,…”
Section: Resultsmentioning
confidence: 99%
“…22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment. 29,33,37,44,46,47,50,56,60,73,76,80,83 Other stigmas experienced by COVID-19 patients included psychological pressure, 62,6672,75,79,81 verbal violence, 20,5052,55,56,59,61,77,83 avoidance, 2224,26,4042,47,54 labeling, 17,19,21,23,27,29,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor access to information about COVID‐19 prevention and control has been reported particularly in low‐ and middle‐income countries, as well as the socially and geographically marginalized communities (Bonnet et al, 2022; McHunu et al, 2022; Wang et al, 2020). Poor access to information was also associated with experiencing more COVID‐19 stigma (Adhikari et al, 2022) and a lack of adherence to measures to combat the pandemic (Lowe et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Disease is one of the most common sources of stigma. During the 2019 coronavirus disease (COVID-19) pandemic, there is no doubt that people infected with COVID-19 were stigmatized around the world (4)(5)(6)(7)(8)(9). This stigma has brought large amounts of psychological and physical distress to COVID-19 patients (10,11).…”
Section: Introductionmentioning
confidence: 99%